2017
DOI: 10.1016/j.cub.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Anterior-Posterior Gradient in Neural Stem and Daughter Cell Proliferation Governed by Spatial and Temporal Hox Control

Abstract: A readily evident feature of animal central nervous systems (CNSs), apparent in all vertebrates and many invertebrates alike, is its "wedge-like" appearance, with more cells generated in anterior than posterior regions. This wedge could conceivably be established by an antero-posterior (A-P) gradient in the number of neural progenitor cells, their proliferation behaviors, and/or programmed cell death (PCD). However, the contribution of each of these mechanisms, and the underlying genetic programs, are not well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 62 publications
3
70
1
1
Order By: Relevance
“…Hox regulation: Hox factors are turned on late in NBs (Baumgardt et al, 2014;Karlsson et al, 2010;Monedero Cobeta et al, 2017), and we find that this may be explained by our finding that Wor, Kr, and Pdm2-Nub act as repressors of Antp. On the other hand, Ase and Hb were activators of Antp, which may help explain the precise onset of Antp in late NBs.…”
Section: Early and Late Factors Are Involved In Extensive Cross-regulmentioning
confidence: 76%
“…Hox regulation: Hox factors are turned on late in NBs (Baumgardt et al, 2014;Karlsson et al, 2010;Monedero Cobeta et al, 2017), and we find that this may be explained by our finding that Wor, Kr, and Pdm2-Nub act as repressors of Antp. On the other hand, Ase and Hb were activators of Antp, which may help explain the precise onset of Antp in late NBs.…”
Section: Early and Late Factors Are Involved In Extensive Cross-regulmentioning
confidence: 76%
“…9). In contrast, grh IM ;Ubx 1 double heterozygous mutant embryos exhibited additional NBs in A1 and A2 segments, revealing a functional cooperation between Ubx and Grh during programmed cell death 56,58,59 . This interaction is of functional importance only in the neural lineage, as the muscle pattern was unaltered in grh IM ;Ubx 1 double heterozygous mutant embryos ( Supplementary Fig.…”
Section: Establishment Of Targeted Bioid In Drosophila Embryosmentioning
confidence: 89%
“…6g, h). Using Dpn stainings as read-out 40,[55][56][57] , we found that single Ubx 1 and grh IM homozygous mutants displayed supernumerary NBs in the A1 segment (Ubx, +4NBs) and in all abdominal segments (Grh), while single heterozygous mutants did not show a significant change in NBs number ( Supplementary Fig. 9).…”
Section: Establishment Of Targeted Bioid In Drosophila Embryosmentioning
confidence: 99%
“…2) Cell cycle exit followed by programmed cell death (PCD) e.g., NB5-6T. 3) PCD e.g., NB7-3 [122,123,127,129,130] (Fig. 17).…”
Section: Temporal Progression Of Neuro-developmentmentioning
confidence: 99%
“…In Drosophila CNS lineages, an NB can exit cell cycle by death, or first exit cell cycle and then die. Both modes are employed to trim the lineage and ensure the generation of the right numbers and types of cells [122,130]. proteins Draper and Simu [154,155].…”
Section: Apoptosis/programmed Cell Death (Pcd)mentioning
confidence: 99%